2018
DOI: 10.3390/ijms19041167
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Adenosinergic Axis in Chronic Lymphocytic Leukemia: A Way to Disrupt the Tumor Niche?

Abstract: Targeting adenosine triphosphate (ATP) metabolism and adenosinergic signaling in cancer is gaining momentum, as increasing evidence is showing their relevance in tumor immunology and biology. Chronic lymphocytic leukemia (CLL) results from the expansion of a population of mature B cells that progressively occupies the bone marrow (BM), the blood, and peripheral lymphoid organs. Notwithstanding significant progress in the treatment of these patients, the cure remains an unmet clinical need, suggesting that nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 153 publications
(197 reference statements)
0
6
0
Order By: Relevance
“…Adenosine-dependent A 3 AR stimulation induces apoptosis in stomach cancer cells via a mechanism that involves PKC activation [52]. An inhibition of tumor growth following receptor stimulation has been demonstrated in lymphoma [51], leukemia, [53] as well as colon [54] and pancreatic carcinoma [55]. Contrariwise, A 3 AR stimulation prompts cell proliferation in other cancer types, such as colorectal cancer and adenocarcinoma [56].…”
Section: The Role Of a 3 Ar In Cancer General Overwiewmentioning
confidence: 99%
“…Adenosine-dependent A 3 AR stimulation induces apoptosis in stomach cancer cells via a mechanism that involves PKC activation [52]. An inhibition of tumor growth following receptor stimulation has been demonstrated in lymphoma [51], leukemia, [53] as well as colon [54] and pancreatic carcinoma [55]. Contrariwise, A 3 AR stimulation prompts cell proliferation in other cancer types, such as colorectal cancer and adenocarcinoma [56].…”
Section: The Role Of a 3 Ar In Cancer General Overwiewmentioning
confidence: 99%
“…Given the important role of NOTCH proteins in a wide range of processes and tissues, aberrations leading to an increase or loss of NOTCH signaling components and functions are associated with a variety of disorders, including solid cancer and hematological malignancies, where NOTCH can act as an oncogene or as a tumor suppressor. Currently, there are many examples that clearly show the relationship of mutations in the Notch1 and Notch2 genes with lymphoproliferative disorders, including chronic lymphocytic leukemia, mantle lymphoma, marginal spleen lymphoma, diffuse B-large cell lymphoma, follicular lymphoma, and Burkitt and Hodgkin lymphomas [65][66][67][68]. According to our data, the patient has an inactivating nonsense mutation p.Y1508* in their NOTCH2 gene as well as a non-synonymous replacement of p.G736V with a pathogenic value.…”
Section: Discussionmentioning
confidence: 52%
“…In healthy tissues, ATP exists mainly intracellularly, up to the millimolar range, whereas in the extracellular space, it occurs at low nanomolar concentrations. 272,273 Hence, ATP-responsive zeolitic imidazole framework-90 (ZIF-90) was reported by lsaiari et al for cytosolic protein delivery and CRISPR/Cas9 genome editing, which could disintegrate and release proteins in the presence of ATP, as a result of the competitive coordination of zinc ions with ATP. 274 Furthermore, studies had shown that ZIF-90/protein NPs could deliver a variety of proteins into the cytoplasm regardless of protein size and relative molecular mass.…”
Section: T1 Cellsmentioning
confidence: 99%